Persepsi Guru Paud Terhadap Mitos Neurosains di Wilayah Lombok dan Bali - Fatmawati; Swastini, Ni Made; Cahyani, Ni Putu Manik Erlin (CAHAYA: Journal of Research on Science Education, 2023)
The purpose of this study was conducted to reveal the perceptions of early childhood education (ECE) teachers towards neuroscience myths. This research uses descriptive qualitative research, namely by using survey research methods. In qualitative research the most important feature comes from natural / real qualitative methods at the interview stage with the help of Google from in the form of questionnaires distributed via WhatsApp social media and observed the results of the respondents. The population in this study were PAUD teachers in the Lombok and Bali regions. With a large sample of 102 PAUD teachers, 51 people from the Lombok region and 51 people from the Bali region. The results showed that teachers' belief in neuromyths is very high, and there are 5 statements of fact that have been understood but the level of understanding cannot be detected. In addition, teachers still have difficulty distinguishing between myths and facts about neuroscience. For this reason, the researcher suggests improving science-based programs by working with teachers and neuroscientists. Teachers will benefit from more accurate brain knowledge and include introductory neuroscience materials in pre-teacher education.